Demographic and Clinical Characteristics of Patients Who Died of Methanol Toxicity During COVID 19 Period in Loghman-e Hakim Hospital in Tehran - Shahin Shadnia; Lida Shojaei Arani; Kiumars Bahmani; Maryam Akhgari; Hoorvash Farajidana; Mohamadreza Ghadirzadeh; Mohammadreza Hajiesmaeili; Omidvar Rezaie Mirghaed (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Outbreaks of methanol poisoning were observed during the COVID-19 pandemic. Acute methanol poisoning is a global crisis. Methanol can cause acute and fatal toxicity through metabolic acidosis. In the present study, we evaluated demographic, clinical, and paraclinical characteristics of patients who died in the recent outbreak of methanol poisoning in Tehran from March to April 2020. Methods: This cross-sectional study was accomplished at the Loghman-Hakim Hospital in Tehran on 80 patients who died of methanol toxicity. Demographic, clinical, and laboratory data were collected retrospectively from the patient’s files and analyzed with appropriate statistical tests. Results: Men were significantly more involved than women (%85 vs. %15). There were no significant differences between other characteristics of male and female patients, including the time between consumption to arrive hospital, dialysis sessions, pulse rate, respiratory rate, loss of consciousness, seizure, acute kidney injury, brain CT, and Intracerebral Hemorrhage ( ICH). Blood sugar, serum potassium, and liver function tests were higher than average in most of the patients. Conclusion: Our study showed that this outbreak of methanol poisoning was due to the use of alcoholic drinks that contain methanol. Men were primarily affected that could be because of the cultural and social status of our country. The greater seizure probability in females could be because of enhancing the NMDA receptor by estrogen. Abnormalities in Alanine aminotransferase (ALT), Aspartate Aminotransferase (AST), and Prothrombin Time (PT) were seen in most patients, indicating liver damage. Misbeliefs about the protective effects of alcohol consumption against COVID-19 may lead many to consume poorly made alcohols that contain methanol and outbreaks of methanol intoxication.